Effects of trimetazidine in acute pancreatitis induced by L-arginine - Yenicerioglu, Akan; Cetinkaya, Ziya; Girgin, Mustafa; Ustundag, Bilal; Ozercan, Ibrahim Hanefi; Ayten, Refik; Kanat, Burhan Hakan (Cma-Canadian Medical Assoc, 2013)
Background: In acute pancreatitis, oxygen free radicals (OFRs) and cytokines have been shown to play a role in the failure of pancreatic microcirculation and the development of local tissue damage. We studied the effects of trimetazidine (TMZ), a potent antioxidant and anti-ischemic agent, on acute pancreatitis. Methods: Rats were randomized into 3 groups: a control group (n = 15), a study group (n = 15) in which acute pancreatitis was induced with with L-arginine, and a treatment group (n = 15) in which pancreatitis was induced and treated with TMZ intraperitoneally. The rats were followed for 24 hours. At the 24th hour we determined serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), amylase, lactate dehydrogenase (LDH), interleukin 1-beta (IL-1 beta), interleukin 6 (IL-6) and tumour necrosis factor-alpha (TNF-alpha), and the pancreatic tissues were analyzed histopathologically. Results: The AST (p < 0.001), ALT (p < 0.01), amylase (p < 0.001), LDH (p < 0.01), TNF-alpha (p < 0.01), IL-1 beta (p < 0.001) and IL-6 (p < 0.001) levels, and pancreatic tissue edema (p < 0.01), hemorrhage (p < 0.05), acinar cell necrosis (p < 0.001) and level of perivascular inflammation (p < 0.01), were significantly lower in the treatment group than the study group. Conclusion: Trimetazidine markedly decreases biochemical and histopathologic changes during the early stages of acute pancreatitis, thus preserving the pancreas histologically.
Keywords: Acute Necrotizing Pancreatitis; Oxygen-Free-Radicals; Double-Blind Trial; Reperfusion Injury; Therapy; Rats; Somatostatin; Pathogenesis; Model; Severity